Challenges for rural America in the twenty-first century - Brown, David L. (David Louis), 1945-; Swanson, Louis E.; Barton, Alan W. (Rural studies series., 2003)
The twentieth century was one of profound transformation in rural America. Demographic shifts and economic restructuring have conspired to alter dramatically the lives of rural people and their communities. Challenges for Rural America in the Twenty-First Century defines these changes and interprets their implications for the future of rural America. The volume follows in the tradition of "decennial volumes" co-edited by presidents of the Rural Sociological Society and published in the Society's Rural Studies Series. Essays have been specially commissioned to examine key aspects of public policy relevant to rural America in the new century. Contributors include: Lionel Beaulieu, Alessandro Bonnano, David Brown, Ralph Brown, Frederick Buttel, Ted Bradshaw, Douglas Constance, Steve Daniels, Lynn England, William Falk, Cornelia Flora, Jan Flora, Glenn Fuguitt, Nina Glasgow, Leland Glenna, Angela Gonzales, Gary Green, Rosalind Harris, Tom Hirschl, Douglas Jackson-Smith, Leif Jensen, Ken Johnson, Richard Krannich, Daniel Lichter, Linda Lobao, Al Luloff, Tom Lyson, Kate MacTavish, David McGranahan, Diane McLaughlin, Philip McMichael, Lois Wright Morton, Domenico Parisi, Peggy Petrzelka, Kenneth Pigg, Rogelio Saenz, Sonya Salamon, Jeff Sharp, Curtis Stofferahn, Louis Swanson, Ann Tickameyer, Leanne Tigges, Cruz Torres, Mildred Warner, Ronald Wimberley, Dreamal Worthen, and Julie Zimmerman.